Auxin influx importers modulate serration along the leaf margin. (27th July 2015) - Kasprzewska, Ania; Carter, Ross; Swarup, Ranjan; Bennett, Malcolm; Monk, Nick; Hobbs, Jamie K.; Fleming, Andrew
Summary Leaf shape in Arabidopsis is modulated by patterning events in the margin that utilize a PIN‐based auxin exporter/CUC2 transcription factor system to define regions of promotion and retardation of growth, leading to morphogenesis. In addition to auxin exporters, leaves also express auxin importers, notably members of the AUX1/LAX family. In contrast to their established roles in embryogenesis, lateral root and leaf initiation, the function of these transporters in leaf development is poorly understood. We report that three of these genes (AUX1, LAX1 and LAX2) show specific and dynamic patterns of expression during early leaf development in Arabidopsis, and that loss of expression of all three genes is required for observation of a phenotype in which morphogenesis (serration) is decreased. We used these expression patterns and mutant phenotypes to develop a margin‐patterning model that incorporates an AUX1/LAX1/LAX2 auxin import module that influences the extent of leaf serration. Testing of this model by margin‐localized expression of axr3–1 (AXR17) provides further insight into the role of auxin in leaf morphogenesis.